Informing whole-farm bundling strategies through innovation readiness and scaling analysis in Malawi - Homann-Kee Tui, Sabine; Tufa, Adane; Manda, Julius; Liben, Feyera; Omondi, John O.; Sseguya, Haroon (2025)
This presentation builds on lessons from the CGIAR Mixed Farming Systems Initiative and related national investments in improved cropping systems, soil health, fertilizer management, digitization, and inclusive service delivery. It aims to sensitize stakeholders to why whole-farm bundling has become central to achieving wider and deeper impact at scale, informed by co-design approaches. We begin by revisiting Malawi’s food system context and the growing pressures shaping what farmers can adopt. Smallholder farmers rarely face a single constraint; rather, they face a stack of interlinked challenges including production, finance, markets, advisory services, land and water governance, and social norms. Whole-farm bundling offers a more appropriate response than isolated technologies by organizing technical, institutional, financial, and social innovations into coherent packages that generate higher and more reliable returns for farmers. Drawing on innovation readiness and scaling analysis, the presentation highlights where Malawi’s agricultural innovation system is more prepared than actual farmer use—particularly for commercial and digital technologies—and where uptake remains higher for accessible, socially embedded options such as intercropping, village savings groups, radio, and farmer clubs. The presentation aims to build shared understanding around three questions: How ready is the innovation system to support bundled solutions? Which innovations and initiatives can be elevated through bundling? And how can actors work together more effectively to move from readiness to widespread, inclusive adoption? These reflections feed directly into the co-design of a practical roadmap for scaling whole-farm bundles in Malawi.